PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. KENCANA PERSADA NUSANTARA - Saputra, Dana; Ningsih, Dewita Suryati; Rahayu, Deny Danar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of compensation, work environment, and leadership on job satisfaction of employees at PT. Kencana Persada Nusantara. As for the population in this study were all employees in the production processing of palm fruit bunches (FFB) at PT. Kencana Persada Nusantara Kab. Rokan Hulu taken in 2015 with the number of employees as many as 153 people, while the method of sampling is done with slovin formula in order to obtain a total sample of 111 people, as well as data analysis using multiple linear regression were processed with SPSS version 18.0. From the testing that has been done, test simultaneous regression (F-test) showed that compensation, work environment and leadership simultaneously positive and significant impact on employee job satisfaction, while the partial test (t-test) compensation, work environment and leadership partially positive and significant effect on employee job satisfaction. It is expected that the leadership of the company in order to motivate its employees to provide proper compensation to make employees loyal and want to remain forever in the company's work and incorporate its employees to social security so that it will increase employee job satisfaction to get more maximal perfomance.Keyword : Compensation, Work Environment, Leadership and Job Satisfaction.